If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 8(x + 2) = -9 + 2x Reorder the terms: -7 + 8(2 + x) = -9 + 2x -7 + (2 * 8 + x * 8) = -9 + 2x -7 + (16 + 8x) = -9 + 2x Combine like terms: -7 + 16 = 9 9 + 8x = -9 + 2x Solving 9 + 8x = -9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + 8x + -2x = -9 + 2x + -2x Combine like terms: 8x + -2x = 6x 9 + 6x = -9 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + 6x = -9 + 0 9 + 6x = -9 Add '-9' to each side of the equation. 9 + -9 + 6x = -9 + -9 Combine like terms: 9 + -9 = 0 0 + 6x = -9 + -9 6x = -9 + -9 Combine like terms: -9 + -9 = -18 6x = -18 Divide each side by '6'. x = -3 Simplifying x = -3
| -2x+6x= | | (x+8)*(x-6)=0 | | 0.2(x+11)=6 | | 3-2a=10-3(2a-3) | | 3(f-10)+2(f-29)=2 | | t=7 | | log(3x-2)=2 | | 1/5(y+12)-6=4 | | f/6+1.2=-3o | | 18+k=-(1+2k)-2 | | 4x-34=2x-123 | | 0.08=0.5x-12 | | 5(3p+1)-1=1 | | x/5+8=10 | | -101=3d-56 | | (2x-3)*(x^2-5x+2)=0 | | -1/2-5y=4 | | -37=12t-85 | | 4b-2(3b-5)=2b+6 | | 3y+25=10 | | 8x+20=80 | | -1.3-9.4=-0.4x+86 | | -5(1+x)=-x-29 | | 231=14-31y | | -4y-1=-5y | | -5(n+10)+5n= | | -x+0.6-2x=-4x-0.6 | | -6u-16=-14-8u | | -35=37-12b | | 8+2(-7n+5)= | | (8x^2-x-2)*(9x^2+8x-1)=0 | | 10b+b+1= |